Impact of cash transfer programs on healthcare utilization and catastrophic health expenditures in rural Zambia: a cluster randomized controlled trial - Mori, Amani Thomas; Mudenda, Mweetwa; Robberstad, Bjarne; Johansson, Kjell Arne; Kampata, Linda; Musonda, Patrick; Sandoy, Ingvild (Frontiers in Health Services, 2024)
Background Nearly 100 million people are pushed into poverty every year due to catastrophic health expenditures (CHE). We evaluated the impact of cash support programs on healthcare utilization and CHE among households participating in a cluster-randomized controlled trial focusing on adolescent childbearing in rural Zambia. Methods and findings The trial recruited adolescent girls from 157 rural schools in 12 districts enrolled in grade 7 in 2016 and consisted of control, economic support, and economic support plus community dialogue arms. Economic support included 3 USD/month for the girls, 35 USD/year for their guardians, and up to 150 USD/year for school fees. Interviews were conducted with 3,870 guardians representing 4,110 girls, 1.5–2 years after the intervention period started. Utilization was defined as visits to formal health facilities, and CHE was health payments exceeding 10% of total household expenditures. The degree of inequality was measured using the Concentration Index. In the control arm, 26.1% of the households utilized inpatient care in the previous year compared to 26.7% in the economic arm (RR = 1.0; 95% CI: 0.9–1.2, p = 0.815) and 27.7% in the combined arm (RR = 1.1; 95% CI: 0.9–1.3, p = 0.586). Utilization of outpatient care in the previous 4 weeks was 40.7% in the control arm, 41.3% in the economic support (RR = 1.0; 95% CI: 0.8–1.3, p = 0.805), and 42.9% in the combined arm (RR = 1.1; 95% CI: 0.8–1.3, p = 0.378). About 10.4% of the households in the control arm experienced CHE compared to 11.6% in the economic (RR = 1.1; 95% CI: 0.8–1.5, p = 0.468) and 12.1% in the combined arm (RR = 1.1; 95% CI: 0.8–1.5, p = 0.468). Utilization of outpatient care and the risk of CHE was relatively higher among the least poor than the poorest households, however, the degree of inequality was relatively smaller in the intervention arms than in the control arm. Conclusions Economic support alone and in combination with community dialogue aiming to reduce early childbearing did not appear to have a substantial impact on healthcare utilization and CHE in rural Zambia. However, although cash transfer did not significantly improve healthcare utilization, it reduced the degree of inequality in outpatient healthcare utilization and CHE across wealth groups. Trial Registration https://classic.clinicaltrials.gov/ct2/show/NCT02709967, ClinicalTrials.gov, identifier (NCT02709967).